The socialist Janus. Juan B. Justo and the issue of symbols in modern Politics (Estudios Sociales, 2018)
The article analyzes the way in which a principal leader of Argentine socialism, Juan B. Justo, conceived the singular place that different manifestations of a significant phenomenon of politics had to occupy: the symbols. It is argued that their assessments and proposals around this problem were always tied to changing junctures, showing an oscillating character and demonstrating the weight of two sources: a widely spread scientific culture and the political culture of Socialism of the Second International. The documentary corpus is made up of a wide range of interventions, to then be compared with the contribution of other voices coming from the Argentine socialism that stress the postulates of said political culture on the place of symbols, in general, and in the Argentine politics of the early twentieth century, in particular.
Keywords: political cultures; Juan B. Justo; nationalism; political symbols; socialism